The constant change : an innovative zero waste fashion design process : a thesis presented in partial fulfilment of the requirements for the degree of Master of Design at Massey University, Wellington, New Zealand - Sharma, Megha (Massey University, 2018)
Waste appears in all the areas of fashion and apparel industry, through manufacturing, overproduction, fast fashion and also over-consumption. Scholars such as Kate Fletcher and Alison Gwilt have cited statistics about the pollution created by the clothing industry and the increasing impact of the fast fashion trend on landfills. This practice led research project exemplifies a zero-waste pattern design process primarily aimed at reducing waste at the pre-consumer stage. In it, I employ an integration of fashion design technologies such as various zero waste techniques in the development of a new pattern design method and textile print. The alternative pattern design method uses Constant and Variable pattern shapes created by cutting straight-sided polygons(1) from set fabric lengths. This method of zero waste cutting becomes more visible with a dissected block print textile design. The cut shapes are draped on the form to derive a range of three innovative garment designs. My design process draws on “three levels of processing – Visceral, Behavioral and Reflective” (Norman, 2004, 2013). This methodology has aided my own development as a designer by blending my own history, culture and experiences into this design process for a more meaningful conscious cognition(2). This aspect and technical design process creates possibilities for other designers in the industry and future applications. (1) Polygon – a plane figure with at least three straight sides and angles, and typically five or more. (2) Meaningful conscious cognition – refers to the reflection or looking back over history, culture and experiences, evaluating the circumstances, actions and outcomes. As a result, this helps make decisions of outweighing the strengths of one aspect over the deficiencies of another.
Figures 1, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21 & 23 have been removed from the thesis for copyright reasons.
Keywords: Fashion design; Sustainable design; Clothing trade; Waste minimization; Environmental aspects; Sustainability